Acute and subacute oral toxicity of propylene glycol enantiomers in mice and the underlying nephrotoxic mechanism. (1st December 2021) - Zhou, Yixi; Zhao, Xijing; Hu, Weiping; Ruan, Fengkai; He, Chengyong; Huang, Jiyi; Zuo, Zhenghong
Abstract: Propylene glycol (PG; 1, 2-propanediol) has been commonly used as a food additive and vehicle in pharmaceutical preparations. PG can form rectus ( R -) enantiomers and sinister ( S -) enantiomers. Herein, Kunming mice were used as the animal model to evaluate the acute and subacute oral toxicity of R -PG, S -PG and RS -PG (1:1 racemic mixture of R -PG and S -PG). The median lethal doses of R -PG, S -PG and RS -PG administered by oral gavage to mice were 22.81 g/kg, 26.62 g/kg and 24.92 g/kg, respectively. In the 28-day oral subacute toxicity study, the body weight, organ weights, serum biochemical, and renal histology were examined. There was no difference in subacute toxicity among R -PG, S -PG and RS -PG. The administration of 1 and 5 g/kg/day PG for 28 days caused nephrotoxicity. The kidney somatic index and levels of blood urea nitrogen exhibited a significant increase. Moreover, the activities of superoxide dismutase, catalase, and glutathione peroxidase significantly decreased after the treatment with PG. The levels of malondialdehyde, tumor necrosis factor α, interleukin 1β, and interleukin 6 significantly increased in the kidney. The results show that the nephrotoxic effects of PG are induced by oxidative stress, and the activation of the inflammatory response is mediated by the NF-κB signaling pathway. Together, these findings provide information on R -PG, S -PG and RS -PG treatments for the risk assessment of toxicity and effects on human health. Graphical abstract: Image 1 Highlights: The LD50 values of R -PG, S -PG and RS -PG were 22.81, 26.62 and 24.92 g/kg, respectively. Oral administration of 1 and 5 g/kg/day PG for 28 days causes nephrotoxicity. R -PG, S -PG and RS -PG cause oxidative stress in the kidney. R -PG, S -PG and RS -PG cause an inflammatory response that is mediated by the NF-κB pathway.